PENERAPAN MODEL PROBLEM BASED LEARNING MENGGUNAKAN LEMBAR KERJA SISWA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH BELAJAR KIMIA SISWA KELAS X DI SMA NEGERI 1 ANGKOLA BARAT - Jennnita Rambe; Abubakar Abubakar; Wiwik Novitasari (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2019)
The research is the research action class. The model used is a model of problem based learning. As for the data collection technique used is the test, observation, interview and question form and data gathering tool used is the test sheet, sheets of observation, the now closed and the format of the interview. The data will be analyzed with descriptive analysis method i.e., first make a list of the frequency of the first. Based on the data analysis done is obtained that the application of the model of problem based learning using worksheets students committed researchers is to improve student learning and activity the performance of teachers. Keyword: Problem Based Learning, research action class, the student's activities